2019
DOI: 10.1039/c9ra90002k
|View full text |Cite
|
Sign up to set email alerts
|

Correction: A new family of fullerene derivatives: fullerene–curcumin conjugates for biological and photovoltaic applications

Abstract: Correction for ‘A new family of fullerene derivatives: fullerene–curcumin conjugates for biological and photovoltaic applications’ by Edison Castro et al., RSC Adv., 2018, 8, 41692–41698.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Due to the special properties of fullerenes, it is currently a prominent topic in many areas of nanomaterial research. There have been many experimental studies using this material to form a drug carrier system and have shown a significant improvement in the pharmacokinetic properties of the active substance 9,10 . Curcumin is a natural compound extracted from turmeric, which has many pharmacological properties such as antiviral, antibacterial, anti-cancer.…”
Section: Science and Technology Development Journal 24(si1):si51-si62mentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the special properties of fullerenes, it is currently a prominent topic in many areas of nanomaterial research. There have been many experimental studies using this material to form a drug carrier system and have shown a significant improvement in the pharmacokinetic properties of the active substance 9,10 . Curcumin is a natural compound extracted from turmeric, which has many pharmacological properties such as antiviral, antibacterial, anti-cancer.…”
Section: Science and Technology Development Journal 24(si1):si51-si62mentioning
confidence: 99%
“…For fullerenes, there are also some computational simulation studies such as the structure, the antioxidant capacity of some polyphenols, and fullerene derivatives (C60) by using the computational chemistry method by Nguyen Minh Thong 12 . Castro E. Cerón and colleagues conducted an experimental study to create externally bound to fullerenes 10 . Although, as we can see in Figure 4, the fullerene derivative with curcumin by Castro E. Cerón et al 10 , the curcumin molecule binds outside the surface of the fullerene.…”
Section: Si52mentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon nano materials (CNMs) including graphene quantum dots (GQDs), carbon nano tubes (CNTs), carbon nano onions (CNOs), and carbon dots (CDs) have been exploited for their wide- spread applications as sensors, in catalysis, tissue engineering and cancer therapy. A relatively recent article revealed the ability of graphene quantum dots (GQDs) to inhibit the fibrillization of the Parkinson’s Disease (PD)-associated amyloid α-synuclein . The GQDs were able to directly interact with mature fibrils and trigger their disaggregation.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, graphitic nanomaterials such as fullerene, carbon nanotubes, and graphene have been widely used in bioanalysis and biomedicine due to their unique physical and chemical properties, versatile natures, and negligible toxicities . To date, a variety of graphitic nanomaterial‐based applications have facilitated the development of biomedical applications, such as carbon quantum‐dot‐based biosensors and imaging systems, graphene oxide‐based biosensors and drug delivery systems, and carbon nanotube‐based therapy applications .…”
Section: Introductionmentioning
confidence: 99%